Siouan materials, C. F. Voegelin Papers - Voegelin, C. F. (Charles Frederick), 1906-1986; Wolff, Hans, 1920-1967 (1925)
There are some materials relating to Siouan languages in the C. F. Voegelin Papers. This entry is intended as a catch-all for materials labeled as Siouan or Macro-Siouan. Researchers should also search for entries for specific Siouan languages and culture groups. Siouan materials are located in both Subcollection I and Subcollection II. In Subcollection I, there is a folder containing a list of of Siouan-Iroquois words in Series V. Research Notes, Subseries V-A: Language Notes. In Subcollection II, correspondence with Hans Wolff concerns work on comparative Siouan and can be found in Series I. Correspondence; there are notes on Siouan in the "Miscellaneous languages" file in Series II. Research Notes, Subseries I. Eskimo-Aleutian; and there is a subseries on Macro-Siouan in the the same series (Research Notes). Subseries IV. Macro-Siouan contains files on Cherokee, Iroquoian, Oneida, and Yuchi grammatical notes.